Differences between winning and losing teams in top-level female beach volleyball - Häyrinen, M.; Tampouratzis, K. (World Congress of Performance Analysis of Sport IX, 2012)
Top-level beach volleyball matches are often very even and the purpose of this study was to analyse technical skills as possible determinants on winning in international top-level female beach volleyball. In total 31 normal (to 21 points) beach volleyball sets played in World Tour 2010 and 2011 and European Championships 2011, were analysed using Data Volley -match analysis software. The teams that played on these matches were placed 3-38 on the World Tour ranking. Serve was analysed using a 6-level scale, reception and attack using a 5-level scale, dig using 3-level scale. Attacks were also divided to attacks after reception and attacks after dig. Also the number of successful blocks and the number of opponent`s errors were analysed. The success and error percentages were calculated for each team in each skill in each set. The normality of every variable was tested using Shapiro-Wilk test and then either t-test for paired samples or Wilcoxon signed-rank test was used to compare the winning and losing teams. The teams that won sets were found to be significantly better in overall attacking (success% 59.8 % vs. 46.2 %, p<.001, error% 11.6 % vs. 18.5 %, p<0.01), attacking after reception (success% 60.7 % vs. 46.5 %, p<.001, error% 11.6 % vs. 18.6 %, p<0.01), transition attacking (success% 53.5 % vs. 45.4 %, p<.01) and blocking (1.5 blocks/set vs. 0.6 blocks/set, p<.001). The set winners had a smaller error percentage in reception (6.7 % vs. 11.3 %, p<.05). On the contrary the success or error percentages for serves (success% 29.0 % vs. 23.6 %, ns., error% 11.0 % vs. 12.5 %, ns.) and digs (success% 65.0 % vs. 64.8 %, ns., error% 23.1 % vs. 24.8 %, ns.) did not differ significantly. The error percentages for transition attacks (10.1 % vs. 17.4 %, ns.) did not differ significantly. Also no significant difference was found in the number of points received from the opponent`s errors (4.7 vs. 4.4 points/set). (Figure 1.) The results suggest that attacking and blocking were the most decisive skills concerning winning in top-level female beach volleyball. Especially the attack after reception considered to be a very important skill. Also the quality of receiving had an effect to winning.